Antimicrobial effects of some dicarbonyl and tricarbonyl sugar hydrazone derivatives - Gabriel, J; Volc, J; Kubátová, E (Folia microbiologica, 1993)
Several dicarbonyl and tricarbonyl sugars were prepared by the use of fungal enzymes and the antimicrobial effects of their N,N-diphenylhydrazine derivatives were tested. G+ bacteria were more sensitive than G- bacteria especially in the group of disubstituted compounds. Peracetyled derivatives were not active. No inhibition of yeast growth was found.
Keywords: Bacillus subtilis; antibakteriální látky; ketosy; Ketoses; Microbial Sensitivity Tests; Phenylhydrazines; Escherichia coli; fenylhydraziny; Anti-Bacterial Agents; mikrobiální testy citlivosti